2016
DOI: 10.1080/22201181.2016.1187497
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine use in surgical patients in a South African tertiary hospital

Abstract: Background: The use of traditional medicine (TM) in South Africa is reportedly high. TM use in a South African surgical population presenting for elective surgery is unknown. Aim: The study aim was to survey the perioperative usage of TM in a South African population presenting for elective surgery at a tertiary hospital. Methods: A prospective, contextual and descriptive study was carried out on adults presenting for elective surgery at a tertiary South African hospital. Results: During a 2 month study period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In the Nigerian study, 40% of 60 patients surveyed used herbal medicine during their preoperative period, 145 while in the South African study 7% of 495 surgical patients had used TCAM in the preceding 6 weeks. 146 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Nigerian study, 40% of 60 patients surveyed used herbal medicine during their preoperative period, 145 while in the South African study 7% of 495 surgical patients had used TCAM in the preceding 6 weeks. 146 …”
Section: Resultsmentioning
confidence: 99%
“…112 Among surgical patients in South Africa, close to one-third (30%) paid less than US$60 for TCAM services. 146 …”
Section: Resultsmentioning
confidence: 99%
“…In the Nigerian study, 40% of 60 patients surveyed used herbal medicine during their preoperative period, 145 while in the South African study 7% of 495 surgical patients had used TCAM in the preceding 6 weeks. 146 Others (infantile colic, tuberculosis, oral health and mycetoma) A study in Nigeria reported that 32.8% and 3.1% use TCAM product and visited a traditional birth attendant to manage infantile colic, respectively. 147 Also, studies conducted in Nigeria reported that 10% and 19.8% of patients suffering from tuberculosis 148 and toothache 149 had consulted with a traditional medicine practitioner, respectively.…”
Section: Surgical Carementioning
confidence: 99%
“…112 Among surgical patients in South Africa, close to one-third (30%) paid less than US$60 for TCAM services. 146 Findings from studies that assessed the cost per month of TCAM use alone reported an average of US$47.5 (US$12.60-US$96.88). 21 25 47 55 167 In comparison between self-treatment and TCAM practitioner use, the average financial cost in Burkina Faso for TCAM self-care (US$2.85) was almost half of that for practitioner use (US$4.77).…”
Section: Cost Of Tcam Usementioning
confidence: 99%
“…Factors associated with traditional medicine use in Africa include lower educational status, knowledge of traditional medicine, low socioeconomic status, older age, large family size, unemployment, and rural residence [6,23,19,35] There is limited information about the use of traditional medicine by women delivering via csection in sub-Saharan Africa. Some patients undergoing other surgeries, including orthopedic, general, and gynecology surgeries, in South Africa reported using traditional medicine during recovery [33]. Additionally, some literature in sub-Saharan Africa reports that women use traditional medicines to get pregnant or during their pregnancies, and there has been an association between traditional medicine use and poor pregnancy outcomes [14,16].…”
Section: Introductionmentioning
confidence: 99%